Fastställande av föräldraskap – Ett område i behov av förändring - Melin,Olivia (2019)
The purpose of this thesis is to examine the current legal position on how to determine paternity, maternity and parentage, and thereafter discuss whether the regulation in the Parental Code is still adequate in today’s society, or if it is in need of alteration. This thesis has its basis in the principle of the child’s best interest. According to applicable law parentage is determined differently depending on formation of cohabitant, gender and sexual orientation. The one who gives birth to a child is the one who is attributed to maternity to the child. Paternity is attributed differently depending on whether the child is born of an unmarried or married woman. If the woman is married, her husband is presumed to be the father of the child by the paternity presumption. If she is not married, paternity is determined by confirmation or verdict. In recent years regulation regarding parentage by assisted fertilization has started to emerge. Maternity and paternity are then determined in the same way as for children who has been conceived by intercourse. For a homosexual same-sex couple, the woman whose partner gives birth to the child is attributed parentage. Parentage is determined by confirmation or verdict, regardless of whether the women are married or not. A number of proposals on how the methods could be altered and modernized has been discussed, both within legislation and in literature. In this thesis I examine the proposals on abolishing paternity presumption, instating presumption for cohabitants and instating parentage presumption. I reach the conclusion that the current legal position in this area is no longer adequate in today’s society since it does not fulfill the principle of the child’s best interest, nor does it provide equal treatment for both parents of the child. Therefore, there is need for new regulation. According to my opinion, the paternity presumption should be abolished. If the paternity presumption is abolished, neither a presumption for cohabitants nor a parentage presumption should be instated. Parentage should be determined by confirmation or verdict for everyone instead, regardless formation of cohabitant or sexual orientation.
Keywords: Familjerätt; civilrätt; föräldraskap